A FAN SPEED CONTROLLER USING IOT BASED ON RASPBERRY Pi AND SMARTPHONE - Wahjudi, Dody; Tri, Watiningsih; Sobirin, Abdul Aziz; Daramawan, Isra' Nuur; Prasetyo, Rahardian Luthfi (Program Studi Teknik Elektro Universitas Peradaban, 2025)
Advences is eletronic techonology have helpen in the development of system that make things easier. One off them is the application of a fan sped control system using a smartphone and knowing number of RPM for each level. This study taks the topic of fan speed control devices and determines the number of rpm for each level using an infrared sensor using an IOT-based nodemcu microcontroller. The purpose of this research is to find out how to design a fan speed control device using an internet of thing-based Raspberry and to find out how the system works on a fan speed control device and find out what the rpm is using an Internet of Things-based Raspberry. The design of a fan speed rpm regulator has been successfully designed and can be applied at home using the IoT system. In the design there is an error of 9.36% at the raspberry input voltage and 17.64% at the raspberry output, 2.3% relay input and 1.84% relay output, 3.4% ESP-01 module input and 1.5 % output on the ESP-01 module, 3.12% infrared input and 65.8% infrared output..